A Comparative Study of Intermolar Arch Width before and after Orthodontic Treatment in Alignment Phase among Class II Div-I Patients - Huma Ejaz, Muhammad Khizar Iqbal, Muhammad Humza, Farah Khan, Jeevat Kumar, Muhammad Anique, (Pakistan Journal of Medical & Health Sciences, 2022)
For an orthodontist, changes in the width of the arch caused by treatment with fixed appliances are important. Understanding these changes is critical to your physician's planning for treatment. Aim: The purpose of the study was to compare and determine the width of the inter- molar arch in cases of class II, division 1 before and 4 months after fixed orthodontic treatment. Study Design: A cross-sectional intervention study. Place and Duration: In the Orthodontics department of Jam Ghulam Qadir Govt. Hospital, Hub Govt of Balochistan and Bhitai Dental and Medical College Mirpurkhas, for six-months duration from July 2021 to December 2021. Methods: 200 Class II Division 1 malocclusion patients were included by the purposive non- probability technique of sampling. 14 to 28 years was the patients age range. The impressions of the upper arch were measured before and six months after orthodontic treatment, and the maxillary inter-molar width was measured. Standard 0.012 Nitinol to 0.019x0.028 arch wires were used. The width of the inter-molar arch was taken as the transverse distance from the central fossa of the 1st molar on one side of the same arch to the central fossa of the 1st molar on the same arch of other side. Results: 200 Class II Division 1 malocclusion patients were included (120 males and 80 females) with 14-28 years of age range and 18.24 ± 2.8 years of mean age. The mean values ​​of the inter-molar width in the entire sample were 46.01 mm ± 2.58 mm in T1 and 48.201 mm ± 2.70 mm in T2 (Table 2). The mean width of the inter-molar arches in men and women before treatment was 43.7± 2.2 mm and 46.2 ± 2.8 mm. Though, the mean T2 inter-molar arch width after treatment was 47.1 ± 2.3 mm in women and 48.3 ± 2.7 mm in men. Conclusion: There was an average rise in the width of the inter-molar arch by 1.7 mm before and after treatment, therefore the orthodontist should consider the mechanics of expanding the arch, especially when the treatment plan does not include extractions. Keywords: width of the inter-molar arch, shape of the arch, malocclusion class II division 1